The Role of Chaplain Activity of Volyn Kyiv Patriarchy Diocese in the Sphere of Medicine - Rostyslav Diduh (Волинський благовісник, 2016)
The author proposes to consider the problem of cooperation with medical institutions of the Church. It was found the concept of "chaplain." Determining the formation of priests, chaplains in hospitals as one of the main conditions for the salvation of the faithful stressed that this process is difficult and developed extensive experience as chaplains in the spiritual and physical support of the faithful and medical staff, opening up new possibilities for the formation of professional skills. An analysis of the author proves how important the care of the Church of medicine.